Personalization of Visual Scene Displays: Preliminary Investigations of Adults With Aphasia, Typical Females Across the Age Span, and Young Adult Males and Females. Issue 3 (July 2021) - Beukelman, David R.; Thiessen, Amber; Fager, Susan Koch
Abstract : Visual scene displays (VSDs) are becoming an increasingly popular method of message representation within augmentative and alternative communication (AAC) supports; however, design factors can influence the effectiveness of these images as communication supports. One issue that has come to light in recent years is the fact that selecting personalized VSDs, which depict the person with complex communication needs or an individual with whom they are familiar, is preferred over generic VSDs, which depict unfamiliar individuals. Although personalization is likely an important factor in the usability of VSDs, these images may be difficult for clinicians to obtain. As such, compromises must be identified. The purpose of this study was to explore the effects of controlling personal relevance factors (i.e., age and gender of the people depicted in generic VSDs) on the image preference patterns of adults with and without aphasia. Results from three very preliminary study summaries indicate that gender and age are both mitigating factors in image preference, as males tended to indicate preference for VSDs containing males over those containing females. In addition, females tended to indicate preference for females of a similar age depicted in VSDs.